An Investigation into the Case of Multi-interpretation in Poetry Translation - Tu, X; Sun, Y (KnE Social Sciences, 2018)
In translating poems, it is very common that different people have quite different versions of the same poem. It therefore intends to expound upon its underlying factors from the perspective of Hermeneutics, by exploring the relation between the textual meaning and the textual significance of a poem, the relation between the author’s intention and the textual intention of a poem, aiming to explain the key element in translating poems—multi-interpretation. Keywords: poetry translation, Hermeneutics, the textual meaning, the textual significance, the author’s intention, the textual intention, multi-interpretation